ANALISIS RISIKO BAHAYA PADA STASIUN LOADING RAMP DAN PEREBUSAN PADA INDUSTRI PENGOLAHAN KELAPA SAWIT DENGAN METODE JOB SAFETY ANALYSIS (JSA) - Sudarma, Ahmad; Suastiyanti, Dwita (Journal of Industrial Engineering and Technology, 2023)
The oil palm plantation industry in Southeast Asia, including PT. Kelapa Sawit plays an important economic role by creating jobs for thousands of people. This research employs the Job Safety Analysis (JSA) approach to recognize potential incidents and suggest the use of suitable personal protective gear (PPE/APD). Accidents on the production floor, such as falls, pinches, or contact with hazardous materials, pose a serious threat to employee safety. In order to achieve this goal, oil palm plantation companies need to continuously improve awareness of K3, identify existing risks, involve workers in safety improvements, and provide the necessary training and support